Promoting Inclusive Islam: The Role of Social Media in Fostering Religious Tolerance in the Digital Era - Supriatna, Hendi; Kuswana, Dadang; Saprudin, Acep (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study explores the role of social media in promoting inclusive Islam and fostering religious tolerance in the digital era. Inclusive Islam, which emphasizes openness, respect for diversity, and peaceful coexistence, serves as a framework for engaging with individuals of different beliefs while maintaining one’s religious identity. Fundamental principles such as tawhid (oneness of God), justice, and compassion form the foundation of inclusivity in Islam. Tolerance in this context refers to accepting religious differences while upholding personal faith, as reflected in the prohibition of religious coercion and the recognition of pluralism. Despite these principles, challenges such as radicalism, misinterpretation of teachings, and the impact of globalization continue to pose barriers to inclusivity. This research employs a qualitative approach, utilizing descriptive analysis of written texts and media case studies, with a focus on literature review and content analysis. Findings indicate that social media platforms—especially YouTube—play a crucial role in disseminating inclusive Islamic narratives. Platforms like Jeda Nulis, managed by Habib Ja’far, actively promote interfaith dialogue, counter religious misconceptions, and present Islam as rahmatan lil ‘alamin (a mercy to all creation). However, the effectiveness of social media in spreading inclusive Islamic values is hindered by algorithmic biases, misinformation, and resistance from conservative groups. Addressing these challenges requires collaborative efforts from media practitioners, religious scholars, and policymakers to strengthen digital religious literacy, support content creators, and optimize social media algorithms. This study contributes to media and religious studies by demonstrating how social media can serve as a strategic tool for fostering interfaith understanding and strengthening religious tolerance in a digitally connected world.